Influence of magnetic field configuration and strength on plasma parameters and efficiency of coatings deposition in magnetron sputtering system - Chunadra, А.G.; Sereda, К.N.; Tarasov, I.K.; Makhlai, V.A.; Kozhukhovskyi, B.M. (Problems of Atomic Science and Technology, 2022)
Paper presents results of evaluation of the influence of the parameters of the additional anode electromagnetic trap for discharge electrons in a magnetron sputtering system. The efficiency of ionization processes is also investigated. It has been shown experimentally that a slight increase of the additional anode magnetic field leads to an increase of plasma density in the discharge on several times. The presence of an anode electromagnetic trap causes additional ionization zones. An increase of anode magnetic field leads to an increase of the average energy of charged discharge plasma particles. As the result, it was observed an intensification of the target material sputtering process as well as an increase of coatings deposition rate. In addition, a slight increase in the magnitude of the anode magnetic field has a positive effect on the quality and purity of the deposited coatings. Представлені результати оцінки впливу параметрів додаткової анодної електромагнітної пастки для розрядних електронів у системі магнетронного розпилення. Також досліджена ефективність процесів іонізації. Експериментально показано, що незначне збільшення додаткового анодного магнітного поля призводить до збільшення щільності плазми в розряді в кілька разів. Наявність анодної електромагнітної пастки викликає додаткові зони іонізації. Збільшення анодного магнітного поля призводить до збільшення середньої енергії заряджених частинок плазми розряду. У результаті спостерігалося посилення процесу розпилення матеріалу мішені, а також збільшення швидкості нанесення покриттів. Крім того, незначне збільшення величини анодного магнітного поля позитивно впливає на якість і чистоту нанесених покриттів.